2020
DOI: 10.1111/cns.13460
|View full text |Cite
|
Sign up to set email alerts
|

Zinc provides neuroprotection by regulating NLRP3 inflammasome through autophagy and ubiquitination in a spinal contusion injury model

Abstract: This is an open access article under the terms of the Creative Commons Attribution License, which permits use, distribution and reproduction in any medium, provided the original work is properly cited.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
32
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 37 publications
(34 citation statements)
references
References 37 publications
(46 reference statements)
2
32
0
Order By: Relevance
“…The changes in some central nervous system cells and related protein factors in the acute phase of spinal cord injury can effectively affect the pathological changes of spinal cord injury and promote wound healing. Anti‐inflammatory environment, the more anti‐inflammatory and antioxidant effects of zinc require further experiments to verify these conjectures and perfect the mechanism of action of zinc 26 . In general, it is clear that zinc is used as conventional antioxidants, and the clinical application of immune‐regulating trace elements provides a reliable theoretical basis and medication recommendations for protection against nerve injury.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…The changes in some central nervous system cells and related protein factors in the acute phase of spinal cord injury can effectively affect the pathological changes of spinal cord injury and promote wound healing. Anti‐inflammatory environment, the more anti‐inflammatory and antioxidant effects of zinc require further experiments to verify these conjectures and perfect the mechanism of action of zinc 26 . In general, it is clear that zinc is used as conventional antioxidants, and the clinical application of immune‐regulating trace elements provides a reliable theoretical basis and medication recommendations for protection against nerve injury.…”
Section: Discussionmentioning
confidence: 99%
“… 31 In previous studies, we found that zinc promotes the recovery of exercise behavior in mice with spinal cord injury. 16 , 26 , 28 , 32 , 33 Recently, ferroptosis was discovered to be involved in spinal cord injury, many oxidation products, and hemoglobin fragmentation 30 ; regrettably, the central nervous system is rich in unsaturated fatty acids, causing ferroptosis to play a pivotal role in the initial stage of injury. 34 , 35 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…All animals were intraperitoneal anesthesia with 50 mg/kg pentobarbital sodium, and the model of SCI was established by the weight-drop method as we previously described [ 22 ]. Briefly, a laminectomy was performed at the T9-T10 level and moderate contusion injury was made by dropping an impactor (2 mm diameter, 12.5 g, 2 cm in height) onto the surface of the spinal cord.…”
Section: Methodsmentioning
confidence: 99%
“…Spinal cord tissues or cells were collected for WB assay as we described previously [ 22 ]. The following antibodies were used: anti-cleaved caspase 3 (1 : 1000, Affinity, USA), anti-Bax (1 : 1000, Affinity, USA), anti-Bcl-2 (1 : 1000, Affinity, USA), anti-PGC- α (1 : 1000, CST, USA), anti-NRF2 (1 : 1000, CST, USA), anti-p-AMPK (1 : 1000, CST, USA), anti-AMPK (1 : 1000, CST, USA), anti-GLUT4 (1 : 1000, Affinity, USA), anti-GLUT3 (1 : 1000, Affinity, USA), anti-HO-1 (1 : 1000, Affinity, USA), anti-NQO1 (1 : 1000, Affinity, USA), anti- β -actin (1 : 1000, Proteintech, USA), HRP-conjugated AffiniPure Goat Anti-Mouse IgG (1 : 10000, Proteintech, USA), and HRP-conjugated AffiniPure Goat Anti-Rabbit IgG (1 : 10000, Proteintech, USA).…”
Section: Methodsmentioning
confidence: 99%